2012
DOI: 10.1002/pi.4410
|View full text |Cite
|
Sign up to set email alerts
|

Collective polyelectrolyte diffusion as a function of counterion size and dielectric constant

Abstract: We report studies of the effect of counterions on the properties of solutions of a strong polyelectrolyte for a wide range of solvent dielectric constant. For this purpose we investigated the dynamic properties of polystyrene sulfonate in N‐methylformamide whose dielectric constant changes significantly with temperature. By means of dynamic light scattering and NMR spectroscopy, polymers of different molecular weights and various counterions were investigated, including large phosphazene counterions P1, P2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Single chain diffusion measurements provide an important test to the microscopic description of polymer dynamics put forward by various theories. , In the context of polyelectrolytes, chain diffusion has been studied primarily in excess salt, zero polymer concentration limit by dynamic light scattering, as well as by NMR, fluorescence methods, and centrifugation in the infinite polymer dilution limit, both in salt-free and excess added salt. ,, Measurements above c * have received far less attention, and most experimental data come from two studies by Oostwal and co-workers, , who investigated the molar mass, polymer concentration, and added salt concentration variation of the diffusion coefficient of NaPSS in D 2 O. Studies on solvent, counterion, and cosolute diffusion in polyelectrolyte and ionomer solutions and gels have also been reported. …”
Section: Introductionmentioning
confidence: 99%
“…Single chain diffusion measurements provide an important test to the microscopic description of polymer dynamics put forward by various theories. , In the context of polyelectrolytes, chain diffusion has been studied primarily in excess salt, zero polymer concentration limit by dynamic light scattering, as well as by NMR, fluorescence methods, and centrifugation in the infinite polymer dilution limit, both in salt-free and excess added salt. ,, Measurements above c * have received far less attention, and most experimental data come from two studies by Oostwal and co-workers, , who investigated the molar mass, polymer concentration, and added salt concentration variation of the diffusion coefficient of NaPSS in D 2 O. Studies on solvent, counterion, and cosolute diffusion in polyelectrolyte and ionomer solutions and gels have also been reported. …”
Section: Introductionmentioning
confidence: 99%
“…The second one is ion pairing, i.e., interaction of counterions directly with a separate chain charge, which is influenced by the type of counterion. Furthermore, rheological measurements, dynamic light scattering, and NMR spectroscopy were used to elucidate the influence of the size of salt counterions and valency on the viscosity in polyelectrolyte solutions. , The experimental data confirmed that larger salt ions cause higher viscosities both for monovalent and for divalent salts and that for ions of a similar size divalent salts increase viscosities as compared to monovalent salts. Ion specificity was also dealt with in several other studies including aqueous ionene polyelectrolytes with bromide and fluoride counterions, , adsorption kinetics of a hydrophobic–hydrophilic diblock polyelectrolyte at the solid–aqueous solution interface, complexation and distribution of counterions in a grafted polyelectrolyte layer, and the temperature variations of the critical micelle concentration of cationic micelles differing in headgroup size and counterion type .…”
Section: Introductionmentioning
confidence: 73%
“…When the salt concentration is low, dynamic light scattering experiments show two relaxation times in the correlation functions. This behavior is denoted as “extraordinary” behavior or slow mode dilemma, described and discussed in many instances in the past years. As the salt concentration was increasing above a certain characteristic concentration, c s *, the correlation functions become single exponential. Below the critical pH, only one sort of particles is detected; 21 nm for the polymer P1, 13 nm for the polymer P2, and almost unchanged 5 nm particles for the polymer P3 were found (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%